HEAT EXPOSURE AND KIDNEY HEALTH: DEHYDRATION, ACUTE KIDNEY INJURY, AND PUBLIC HEALTH STRATEGIES IN A WARMING CLIMATE - Kuczyńska, Sandra; Siusta, Natalia; Mehal, Kinga; Pielich, Weronika Martyna; Gałan, Katarzyna; Balicka-Dworczak, Natalia; Kosiło, Dominika (International Journal of Innovative Technologies in Social Science, 2026)
Background: Heat exposure is increasingly recognized as an environmental and occupational health concern with clinically relevant consequences for kidney health. The kidneys are particularly vulnerable to heat-related physiological stress because dehydration, reduced effective circulating volume, renal hypoperfusion, and tubular stress may contribute to acute kidney injury, especially in susceptible individuals. Methods: This narrative review synthesizes peer-reviewed articles and public health documents identified through PubMed/MEDLINE, PMC, and institutional sources, including the World Health Organization and occupational health agencies. Priority was given to recent reviews, epidemiological studies, mechanistic papers, occupational health studies, and public health guidance relevant to heat-related kidney injury and prevention. Results: Evidence indicates that high ambient temperature is associated with kidney-related morbidity, including acute kidney injury. Risk is particularly relevant among older adults, patients with chronic diseases, people using medications affecting fluid balance or renal perfusion, outdoor and manual workers, and physically active individuals. Repeated heat stress and dehydration may also contribute to chronic kidney disease risk in occupationally exposed populations, although causality and the relative contribution of environmental, occupational, and social determinants remain under investigation. Conclusions: Heat-related kidney injury should be approached as a partially preventable clinical and public health problem. Prevention should extend beyond individual hydration advice and include clinical risk identification, medication awareness, occupational heat protection, access to cooling and safe drinking water, heat-health warning systems, and equity-oriented strategies for populations with limited control over heat exposure.